2014
DOI: 10.1186/1810-522x-53-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulation in captive broad-snouted caiman (Caiman latirostris)

Abstract: Background: Crocodilians are ectothermic animals. For this reason, the environmental temperature has substantial effects on their physiology and behavior. The thermoregulatory behavior of these animals involves the selective use of different types of environments. This behavior enables them to reach the temperature level for their metabolic activities. This study aimed to determine the influence of sex, body size, and reproductive stage on the body temperature (T b ) of adult broad-snouted caiman (Caiman latir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…C. latirostris is an opportunistic predator that inhabits wetlands in tropical and subtropical South America (Scott et al, 1990). Bassetti et al (2014) studied the thermoregulation in captive broad‐snouted caiman under resting conditions and verified that the maximum body temperature reaches 31°C between 2:00 p.m. and 7:00 p.m. at rest conditions. There have been relatively few reports on mechanisms underlying the SDA in crocodilians.…”
Section: Introductionmentioning
confidence: 95%
“…C. latirostris is an opportunistic predator that inhabits wetlands in tropical and subtropical South America (Scott et al, 1990). Bassetti et al (2014) studied the thermoregulation in captive broad‐snouted caiman under resting conditions and verified that the maximum body temperature reaches 31°C between 2:00 p.m. and 7:00 p.m. at rest conditions. There have been relatively few reports on mechanisms underlying the SDA in crocodilians.…”
Section: Introductionmentioning
confidence: 95%
“…'Heated' and '4 h post-heating' group mussels were emersed and exposed to heat stress using an electric coil heater and a Micro-Infinity temperature controller (Newport Electronics, Santa Ana, CA, USA). Temperature was ramped at +7°C h −1 from 15°C to 36°C to simulate solar heating on a hot day during low tide (Tomanek and Somero, 1999;Lockwood et al, 2010;Denny et al, 2011). The mussels were held at 36°C for one additional hour before the heated group was dissected.…”
Section: Gill Osmolyte Contentsmentioning
confidence: 99%
“…Alternatively, the correlation of taurine content and individual thermal history could relate to taurine's role as a prominent osmoregulatory agent (Lange, 1963). Heat stress has been documented to impair osmoregulatory ability (Tang et al, 2014), and the maintenance of active osmoregulation has been hypothesized to contribute to thermal tolerance (Jian and Huang, 2001;Xu et al, 2013). Further mechanistic work is required to document the relative importance of these various putative benefits of taurine accumulation under episodic exposure to thermal stress.…”
Section: Taurine As a Thermoprotective Osmolytementioning
confidence: 99%
“…In A. mississipiensis and C. acutus, the optimum temperature range for feeding is considered to be between 25 and 35°C (Lang, 1979;Turton et al, 1997). The optimum temperature range for C. latirostris is between 23°C and 35°C (Basetti et al, 2014), but the results reported suggest that caimans perform better at higher temperatures. Other authors reported enhanced growth in C. latirostris at high temperatures.…”
Section: Figurementioning
confidence: 99%